PERAN EMOTIONAL EXHAUSTION DALAM HUBUNGAN ANTARA JOB INSECURITY DAN WORK ATTITUDE: STUDI PADA SALESPERSON OTOMOTIF - Ratih Indriyani; Andrew Gunawan; Sesilya Kempa (MANAJEMEN, 2024)
Salesperson has an important role in the company continuity. Work attitude is one thing that supports the performance of salesperson as the spearhead of the company's marketing. This study was conducted with the aim of understanding the effect of job insecurity on work attitude with the mediation emotional exhaustion. The method used is quantitative, with 106 respondents. The population in this study was automotive sales in Surabaya. This study used a purposive sampling technique. The sample criteria were automotive sales who worked in Surabaya industry for at least 1 year. The results of the study showed that job insecurity did not have a significant effect on work attitude. Job insecurity has a positive effect on emotional exhaustion of automotive sales in Surabaya, while emotional exhaustion has a negative effect on the work attitude of automotive sales in Surabaya. Also, Job insecurity has a negative effect on work attitude through emotional exhaustion of automotive sales in Surabaya.